Seasonal genetic variation in house fly populations, Musca domestica (Diptera: Muscidae) - Tripathi, M.; Agrawal, U. R.; Tewari, R. R. (Cellular and Molecular Biology, 2011)
Seasonal genetic variation was assessed in the common house fly Musca domestica. Allozymes at six gene enzyme system viz., ACPH, EST, G6PD, ME, AO and XDH were analyzed. Fourteen loci with twenty seven alleles were unraveled. The genetic variations were found to be affected to a great extent by environmental influence .F statistics has been used to calculate genetic variation which revealed that very little genetic variation has occurred among the house fly populations analyzed in the present study. Further, except ACPH-2, G6PD-2 and XDH-1 all the other loci show inbreeding (Fis>Fst). Thus it appears that the house fly populations analyzed are characterized by high level of inbreeding. Nei’s genetic identity (I) and distance (D) values reveal a close similarity between summer and rainy season collections.